Pengaruh E-Modul Berbasis Guided Discovery Terhadap Pengetahuan Faktual, Konseptual, dan Prosedural pada Pembelajaran IPA Kelas V - Rahayu, Anisa; Widi Winarni, Endang; Koto, Irwan (Jurnal Pembelajaran dan Pengajaran Pendidikan Dasar, 2024)
This study aims to analyze the effect of guided discovery-based e-modules on the mastery of factual, contextual and procedural knowledge of "digestive organs" in fifth grade elementary school students. This research is quantitative research. The subjects of this research were 23 students of SDN 04 Bengkulu Selatan class VB and 23 VC students. This research uses pretest and posttest questions on factual, context and procedural knowledge. The research results showed that the N-Gain value for factual knowledge was 65.5 in the medium category, the N-Gain value for conceptual knowledge was 59.5 in the medium category, the N-Gain value for procedural knowledge was 52 in the medium category. Based on the research results, it can be concluded that there is a significant influence of learning using science guided discovery-based e-modules on the mastery of factual, conceptual and procedural knowledge.